Three 'D's: Design approach, dimensional printing, and drug delivery systems as promising tools in healthcare applications. Issue 11 (November 2021) - Rahman, Mahfoozur; Almalki, Waleed H.; Alghamdi, Saad; Alharbi, Khalid S.; Khalilullah, Habibullah; Habban Akhter, Md.; Keshari, Amit K.; Sharma, Nisha; Singh, Tanuja; Soni, Kriti; Hafeez, Abdul; Beg, Sarwar
Highlights: QbD application gained wider acceptability in dosage forms development. 3D, 4D, and 5D printing are preferable technology over other tool. The human-sized biomaterial self-assembling are developed by printing technology. Utilizing printing application, developed stent and orthodontic instruments. DDD technology will be gain more diversity in health care applications. Abstract: The development of pharmaceutical drug products is required for the treatment of disease, which has resulted in an increasing number of approvals by regulatory agencies across the globe. To establish a hassle-free manufacturing process, the systematic use of a quality-by-design (QbD) approach combined with process analytical technology (PAT) and printing techniques can revolutionize healthcare applications. Printing technology has been emerged in various dimensions, such as 3D, 4D, and 5D printing, with respect to their production capabilities, durability, and accuracy of pharmaceutical manufacturing, which can efficiently deliver novel patient-centric healthcare products with holistic characteristics. In this review, we provide current trends in pharmaceutical product development using a design approach and high-quality printing techniques.